Effective removal of methyl green from aqueous environment using activated residual Dodonaea Viscosa: equilibrium, isotherm, and mechanism studies. Issue 1 (31st December 2023) - Alorabi, Ali Q.; Azizi, Mohamed
ABSTRACT: In this study, activated residual Dodonaea Viscosa (ARDV) was synthesized by the simple chemical activation process as a cost-effective and sustainable adsorbent for the efficient elimination of methyl green molecule (MG) from water. The prepared ARDV was characterized by TGA, SEM, EDX, FTIR, and BET surface area analysis. The adsorption properties and mechanisms toward MG were examined using the batch method. The optimal conditions for adsorption of Pb(II) were pH= 6.6, [ARDV] =0.1 g, time=180 min, and temperature= 65°C. The adsorption isotherms and kinetics study was conducted and the resulting data fitted well with Langmuir and PSO model. The maximum sorption capacity of 99 mg/g was obtained from Langmuir isotherm for MG at 60 °C. According to thermodynamic parameters, the adsorption of MG on ARDV was endothermic and spontaneous. Hence, it could be concluded that ARDV is an inexpensive and effective bio-adsorbent for the removal of MG from polluted water.